(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
National healthcare systems are increasingly exploiting the benefits of Internet of Things technologies: cloud-connected devices equipped with perceptual sensors can collect highly accurate health data from people even if they do not visit a hospital or private clinic. For potential innovators of new IoT medical devices, the applicable legal framework was so far limited to the application of the General Data Protection Regulation and the Medical Devices Regulation. This article will analyse what will happen when medical data generated by the IoT is shared to create new products or services under the framework now described by the Data Act (DA) and the European Health Data Space (EHDS). As the EHDS and the Data Act both aim at facilitating the secondary use of (health) data, the contribution will compare the two processes established to establish a roadmap for solving the theoretical and practical issues related to health data sharing.